Gender, Nation and Embodiment in Byron’s Poetry - Ray Murray, Padmini (My University, 2008)
This thesis will examine how the concepts of gender and nation were inextricably linked for Byron, and how this is demonstrated in his poetry through strategies of gendered embodiment. Byron’s complex relationship with and attitudes towards women displays an ambivalence that characterises his representations of England, due to his perception of the British body politic as a “gynocrasy.” This ambivalence was further exacerbated by Byron’s conception of his own masculinity as one in flux. His literary professionalisation and his status as an outmoded aristocrat contributed to these anxieties regarding his masculine subjectivity. Byron’s poetic fame was particularly influenced by the growing importance of women as readers, writers and arbiters of literary taste in early nineteenth century England. The first chapter will explore Byron’s anxiety about this increased influence of women as competitors and consumers in the literary marketplace, and how this threat manifests in his monstrous configurations of the female body and the body politic in his poetry. Chapter 2 investigates the tensions between Byron’s cosmopolitanism and patriotism in the context of his masculine subjectivity and demonstrates how these tensions shaped Byron’s first commercially successful work Childe Harold’s Pilgrimage. This chapter also examines how Byron uses this masculine subjectivity in his Turkish Tales in order to assert the authority of his opinions on female sexuality and freedom over those expressed in female-authored works with similarly "exotic" themes. Chapter 3 addresses the post-exilic Byron and how his estrangement from England destabilises his conceptions of subjectivity and influences the poetics of the third canto of CHP. This chapter then goes on to track Byron’s recovery from this disintegration and traces how Byron’s poetic voice takes a new direction in his depictions of gender and nation. He begins to depend more heavily on allegory as a strategy of displacement for his feelings of nostalgia and homesickness and in order to place himself in a national literary tradition, as illustrated in his treatments of women and nation in Don Juan. The fourth and final chapter explores Byron’s feelings towards the domestic and commercial worlds both of which he held as bastions of female authority. Byron examines the ramifications of female influence through the heroines who use sexuality as an assertion of this power against a hapless Juan. This chapter will examine his poem The Island and the poems written just before his death in Greece to demonstrate conclusively how Byron’s struggles to recover his masculine subjectivity are persistently staged as contestations of space.
Keywords: English literature; Byron; gender; nationality